2021
DOI: 10.3390/ma14174824
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Civil Structures through the Application of Smart Materials: A Review

Abstract: Every year, structural flaws or breakdowns cause thousands of people to be harmed and cost billions of dollars owing to the limitations of design methods and materials to withstand extreme earthquakes. Since earthquakes have a significant effect on sustainability factors, there is a contradiction between these constraints and the growing need for more sustainable structures. There has been a significant attempt to circumvent these constraints by developing various techniques and materials. One of these viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…On average we find that every month of full lockdown reduced the demand by 20% on average, or over 1.5% on an annual basis [5]. Therefore, focusing on methods to optimize the energy efficiency and promoting sustainability in the building's component while considering the quality of indoor spaces has been one of the trend topics among researchers [6][7][8][9][10][11][12][13]. In Iran, artificial lighting is reported to contribute up to 25% of electricity consumption in office buildings [14].…”
Section: Introductionmentioning
confidence: 99%
“…On average we find that every month of full lockdown reduced the demand by 20% on average, or over 1.5% on an annual basis [5]. Therefore, focusing on methods to optimize the energy efficiency and promoting sustainability in the building's component while considering the quality of indoor spaces has been one of the trend topics among researchers [6][7][8][9][10][11][12][13]. In Iran, artificial lighting is reported to contribute up to 25% of electricity consumption in office buildings [14].…”
Section: Introductionmentioning
confidence: 99%
“…It can be conclude of those results that: (1) The strain development of the original reinfor similar, which shows that all the strengthening methods of the spec play to the material properties of the original reinforcements, and the mances of the strengthened specimens are good. (2) The strain develo ments in the enlarged section is also relatively stable in the elastic stag of load, the reinforcement of SJ-1 yields first, followed by SJ-2 and SJ-4 ment of SJ-3 yields last. This shows that ECC in the enlarged section tensile force, which makes the reinforcements in the tensile area yie prove its recovery ability.…”
Section: Mechanical Performance Of Reinforcementsmentioning
confidence: 91%
“…It can be concluded from the analysis of those results that: (1) The strain development of the original reinforcements is basically similar, which shows that all the strengthening methods of the specimens can give full play to the material properties of the original reinforcements, and the mechanical performances of the strengthened specimens are good. (2) The strain development of reinforcements in the enlarged section is also relatively stable in the elastic stage. With the increase of load, the reinforcement of SJ-1 yields first, followed by SJ-2 and SJ-4, and the reinforcement of SJ-3 yields last.…”
Section: Mechanical Performance Of Reinforcementsmentioning
confidence: 96%
See 1 more Smart Citation
“…Apart from this, Liang et al [ 3 ] used cables composed of SMA wires to enhance the effectiveness of a friction sliding bearing. A review and detailed summary of the related applications can be found in [ 4 , 5 , 6 ]. SMAs are also being used in other dynamic systems, such as in aeronautic [ 7 ] and automotive [ 8 ] engineering.…”
Section: Introductionmentioning
confidence: 99%